Synthesis and luminescent properties of strontium aluminates activated with bismuth ions - Shevchenko, Gvidona P.; Bokshyts, Yuliya V.; Zhuravkov, Viktor A.; Shishko, Galina V.; Kovel, Ekaterina A. (Journal of the Belarusian State University. Chemistry, 2022)
The Bi-activated strontium aluminates SrAl2O4 and Sr3Al2O6 are synthesised by the solid-phase method; their structural phase and spectral-luminescent properties are studied. The possibility of controlling the luminescence spectrum, its intensity and, consequently, the colour characteristics of the samples by changing the composition of the matrix, the nature of the activator and its concentration are shown.
Keywords: strontium aluminates; solid phase synthesis; bismuth oxides; luminescence